THE EFFECT OF HEALTH INSURANCE ON ASTHMA CONTROL IN RESPONDENTS WITH ASTHMA IN YOGYAKARTA, INDONESIA - Rita Suhadi; Fenty Fenty; Dita Maria Virginia; Christianus Heru Setiawan (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2018)
Asthma is a chronic disease with recurrent breath shortness. Until now, there is no particular therapy to cure the disease and long-term treatment is needed to control the disease. Health insurance has the benefit to support the asthma therapy. This study aimed to assess the effect of health insurance on the asthma control based on Asthma Control Test (ACT) score. The study was done with a cross-sectional design on respondents with asthma who agreed to sign informed consent forms in Yogyakarta. The asthma respondents (n=36) were selected non-randomly, consisting of 23 respondents with health insurance, including universal health coverage or UHC (n=15), UHC and private insurance (n=7), and private insurance only (n=1). The ratio and categorical data were analyzed with the independent T-test or Mann-Whitney test and chi-square statistics, respectively. The study demonstrated that the profiles and number of medicines were similar between groups, except for lower smoking proportion among health insurance groups; the respondents with and without health insurance had the median ACT score at 22 (partial control) and 15 (bad control) respectively, though the scores were not statistically different. Conclusion: the asthma respondents with and without health insurance were not statistically different in the asthma control.